Magnetoelectric response of bismuth-substituted ferrite-garnet films irradiated by a high-power laser pulse - Koronovskyy, V.E. (Functional Materials, 2009)
The electromagneto-optical (EMO) effect as magnetoelectric response for bismuth-substituted ferrite-garnet film exposed to an external electrical field have been investigated. It was shown that irradiation of the film by a high-power neodymium laser results in increase of the EMO characterics that may result from removal of pressure inhomogeneites or local mechanical strains in ferrite-garnet films.